DAMPAK PERCERAIAN TERHADAP ANAK (STUDI KASUS 5 KELUARGA DI KOTA BANGKINANG KABUPATEN KAMPAR) - Nova Yulia Anggreini; Syafrizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Divorce is a divorce between living spouses as a result of their failure to execute the bond role respectively. divorce is disconnecting valid marriage, which had been built. Divorce is sometimes considered plagues because divorce can decide between a husband and wife had the family each and can shake the stability of the child's soul and agitate the society. The purpose of this research is to know the causative fakor divorce and to explain the impact of divorce on the town of Kampar Regency Bangkinang. Usability research is as the image thought to family divorced in the occurrence of divorce can impact on children in the community town of Kampar Regency Bangkinang as well as being a benchmark in finding and formulating factor causes divorce. Location of the study, the authors will discuss the divorced family in the town of Kampar Regency Bangkinang. To obtain data with census methods authors use the technique of data collection with interviews in depth. Data obtained further processed in qualitative descriptive analyst. The results of this research found that the infidelity cause factor who conducted the husband becomes the largest factor which led to the divorce in the city of Bangkinang District of Kampar, the second factor, economic selfishness fakor Thirdly, family intervention the fourth factor and domestic violence factor five. The above can be inferred from the fact that the divorce caused by her husband's infidelity, which factor in children as the impact the occurrence of divorce parents, further the impact of divorce impact on psychology, economics, and education all the above influential impact on the development of children running their lives.Keywords: Divorce, Divorce Cause Factor, Impact On Children